Assessment practices in the policy and politics cycles: a contribution to reflexive governance for sustainable development?. Issue 6 (2nd November 2018) - Meadowcroft, James; Steurer, Reinhard
ABSTRACT: This article examines systematic assessment practices linked to sustainable development policies. We consider five types of assessment—monitoring, policy evaluation, formal audit, peer review, and specialist reporting—and explore their fate in the policy and electoral politics cycles. In contrast to traditional views of the policy cycle, we note that systematic assessments provide complementary feedback around the entire policy cycle. However, despite this omnipresence, their policy relevance is usually severely limited, inter alia because the policy cycle captures only parts of the political reality. A major concern for politicians (but not necessarily for policy or governance scholars) that goes far beyond the formulation and implementation of policies is the broader cycle of electoral politics that determines the state's political personnel as well as government priorities. Here, we highlight that the findings of systematic assessments are often lost in a cacophony of voices to which politicians are more carefully attuned, such as media responses and opinion polls, implying that scientific evidence is simply 'overwritten' with other kinds of evidence representing alternative rationalities and priorities. Despite numerous shortcomings, the true value of systematic assessment practices lies in their potential to furnish ammunition to state and non-state actors interested in securing change.